2018
DOI: 10.1002/nau.23508
|View full text |Cite
|
Sign up to set email alerts
|

An International Urogynecological Association (IUGA)/International Continence Society (ICS) joint report on the terminology for the assessment of sexual health of women with pelvic floor dysfunction

Abstract: A consensus-based terminology report for female sexual health in women with pelvic floor dysfunction has been produced aimed at being a significant aid to clinical practice and a stimulus for research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(123 citation statements)
references
References 185 publications
(231 reference statements)
2
106
0
10
Order By: Relevance
“…In general population-based studies, the prevalence of constipation ranges from 2.6% to 26.9%, with the female gender and age highlighted as contributing factors. 38 Despite the low number of studies that investigated constipation in this review, its prevalence was found to be slightly higher in nurses than in the general population. However, considering that in all three studies, toileting behavior and liquid consumption were significant aspects associated with LUTS, it is possible that these habits may also play a role in the development of constipation.…”
Section: Iciqui-sfmentioning
confidence: 70%
“…In general population-based studies, the prevalence of constipation ranges from 2.6% to 26.9%, with the female gender and age highlighted as contributing factors. 38 Despite the low number of studies that investigated constipation in this review, its prevalence was found to be slightly higher in nurses than in the general population. However, considering that in all three studies, toileting behavior and liquid consumption were significant aspects associated with LUTS, it is possible that these habits may also play a role in the development of constipation.…”
Section: Iciqui-sfmentioning
confidence: 70%
“…All these patients were symptomatic for dyspareunia and "hispareunia." 22,23 In these patients, we partially removed F I G U R E 1 Progress of patients across the study period. FU, follow-up; TVT-O, tension-free vaginal tape-obturator; USI, urodynamic stress incontinence the exposed sling and we resuture the vagina.…”
Section: Resultsmentioning
confidence: 99%
“…The FSFI is a 19-item self-reported questionnaire that assesses multiple dimensions of sexual function. 69,70 The FSDS-R is a 13-item scale that assesses distress related to low sexual desire. 69,71 Treatment of FSD ranges from lifestyle modifications, nonpharmacologic and pharmacologic therapies ( Table 3).…”
Section: High Tone Pelvic Floor Dysfunctionmentioning
confidence: 99%
“…Estrogen can be administered orally, transdermally or vaginally (creams, tablets or rings), and it may improve sexual desire and arousal, and decrease dyspareunia. 8,70,84 Ospemifene (Osphena) is a selective estrogen receptor modulator that acts as an estrogen agonist in the vaginal epithelium. It can be used to treat dyspareunia associated with vaginal atrophy.…”
Section: High Tone Pelvic Floor Dysfunctionmentioning
confidence: 99%